Factors Affecting Purchase Intention on Roasted Coffee Beans (Study Case: Caracal Coffee Roasters) - Rizha Al Fajri (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2023)
This research investigates the effect of product attributes, brand awareness, advertising, sales promotion, and Word of mouth on coffee products' purchase intention. In this case, the coffee products used are Caracal coffee roasters. This research conducted preliminary interviews and a questionnaire for gathering the data. Then, the data is analyzed using narrative analysis for the data from the interview and SEM (structural equation modeling) for the data from the questionnaire. Based on the results of the interviews, most of the respondents agree that Price, Origin, Post-harvest process and Tasting notes are the essential attributes of coffee beans for consumers. Based on the SEM analysis, all five variables, except advertising, significantly influence the Caracal coffee roasters products. Future studies should pursue more variables, especially digital marketing factors and influencers done massively in this era.